Combat-related pelvic ring fractures in survivors. Issue 2 (March 2017) - Purcell, Richard L.; McQuade, Maximilian G.; Kluk, Matthew W.; Gordon, Wade T.; Lewandowski, Louis R.
Abstract : Background: Pelvic fractures have been associated with rates of mortality up to 20%, with open injuries approaching rates up to 50%. This study compares differences in patients with open and closed pelvic ring injuries sustained during combat. Methods: Retrospective review of 114 patients who sustained a pelvic ring fracture and were alive upon presentation to the United States. We collected demographics, associated injuries, transfusion requirements, and outcomes to include residual bowel or bladder dysfunction and ambulatory status. Results: There were 114 patients, 98% male, with 75 closed and 39 open injuries. Average age was 26.6 yr. An average of 8.1 and 28.1 units of red blood cells were transfused in closed and open injuries, respectively ( P <0.0001). Bilateral lower extremity amputations occurred in 11% of closed and 59% of open injuries ( P< 0.0001). Unstable fracture patterns occurred in 39% of closed fractures compared to 51% in open fractures ( P =0.233). The time to weight bearing was 93 and 126 days for closed and open injuries ( P= 0.039). At latest follow-up, abnormal bladder and bowel function both occurred in 10% of closed and, respectively, 39% and 33% of open injuries ( P =0.006). The rate of ambulation was 94% for closed injuries and 89% for open injuries ( P =0.439). Conclusions: In the largest report of combat-related pelvic fractures in surviving patients, the incidence of open fractures was 34%. Although there are significant differences in associated injuries, transfusion requirements and time to weight bearing, patients with open pelvic fractures are able to return to a similar level of ambulatory function as those with closed fractures.